The 2011 humanitarian intervention in Libya: from just intervention to just peace? - Mokwele, Tshepho Joseph (My University, 2017)
This research report analyses the 2011 humanitarian intervention in Libya and seeks to establish whether or not it was morally justified and if it led to a better state of peace (a just peace). It analyses the intervention through the prism of just war theory and the responsibility to protect (R2P) doctrine. Just war theory and the R2P doctrine provide moral guiding principles that must be met to justify the resort to war, its conduct and termination. These principles are outlined in just war theory as jus ad bellum, jus in bello, and jus post bellum. The report highlights the origin and evolution of just war theory vis-à-vis to the practice of humanitarian intervention. Humanitarian intervention has long been prohibited by established international law which, nevertheless, provides for the protection of fundamental human rights. Ingrained in international law are the Westphalian principles of state sovereignty and non-interference that have created a tension between the rights of the states and those of individuals. While international law explicitly states that countries have the right to individual or collective self-defence, it implicitly advocates for humanitarian intervention where a state is unable or unwilling to protect its people. The study, therefore, adopts the notion of sovereignty as responsibility as revived by R2P. It holds that every state ultimately derives its rights from those of individuals: the former forfeits its rights when and if it violates those of the latter. In such a case, a state loses its sovereign standing and becomes liable to humanitarian intervention. The decline in interstate conflicts and the rise of intrastate conflicts since the end of the Cold War reignited the debate around the legality and legitimacy of humanitarian intervention because no universally accepted enabling framework has hitherto existed. But in 2001, the International Commission on Intervention and State Sovereignty (ICISS) published the R2P report that serves as a generally accepted framework for humanitarian intervention today, following its unanimous endorsement by states at the UN World Summit in 2005. This study, however, that while the ICISS R2P is broad and encompasses the responsibilities to react, prevent, and rebuild, the UN R2P is narrow and lacks the post-war reconstruction element. But this is not new: the jus post bellum element of just war theory has historically received little attention in the literature, which has affected its practice. A similar trend is developing with the R2P and the case of Libya is illustrative of that. The study’s application of just war theory and R2P propositions to the Libyan situation establishes that the intervention was morally justified for it prevented the massacre of Libyans by the Qaddafi regime but did not lead to a better state of peace mainly because it was not followed up with post-intervention reconstruction. Failure to consider post-intervention reconstruction in Libya, however, does no damage to the practice of humanitarian intervention. Rather, it serves as a lesson from which to learn and indicates that jus post bellum is integral to just war theory just as the responsibility to rebuild is to R2P in theory and practice.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts in Political Studies to the Faculty of Humanities at the University of the Witwatersrand, Johannesburg.
Keywords: Internation (International law); Humanitarian intervention; Just war doctrine